2021
DOI: 10.1039/d0na00773k
|View full text |Cite
|
Sign up to set email alerts
|

Dendronized vesicles: formation, self-organization of dendron-grafted amphiphiles and stability

Abstract: The impact of dendron generation and concentration on nanoparticles encompassing dendron-grafted amphiphiles along with the mechanisms underlying the stability of these nanoparticles are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…These attractive electrostatic interactions induce the dendron branches to adopt conformations which allow the terminal groups to approach the vesicle surface (Figure 1). 21 To better understand the degree of intermeshing of the branches, the conformation of the dendrons is investigated. For acidic conditions, the dendron branches have two responses to an increase in their relative concentration: (a) the branches extend away from the surface of the vesicle (see Figure S7) and (b) the branches slightly reduce their effective size (see Figure S8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These attractive electrostatic interactions induce the dendron branches to adopt conformations which allow the terminal groups to approach the vesicle surface (Figure 1). 21 To better understand the degree of intermeshing of the branches, the conformation of the dendrons is investigated. For acidic conditions, the dendron branches have two responses to an increase in their relative concentration: (a) the branches extend away from the surface of the vesicle (see Figure S7) and (b) the branches slightly reduce their effective size (see Figure S8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Long-range electrostatics using techniques such as particle mesh Ewald (PME) summation , is not employed due to the large system sizes. In an earlier study on dendronized vesicles, it is shown that the inclusion of PME does not significantly impact the results.…”
Section: Materials and Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The current library of Martini polymers comprises more than 50 different polymers. The models available range from simple linear polymers such as PEO (Figure 1D), [ 14,30,35–37 ] nylon‐6, [ 38 ] and PS, [ 28,29,39–41 ] over branched and hyperbranched polymers such as (grafted) polyamidoamine (PAMAM) [ 42–48 ] or polyethylenimine (PEI) dendrimers, [ 49–52 ] to conjugated polymers such as poly(3‐hexylthiophene) (P3HT, Figure 1F) [ 53 ] and block copolymers [ 32,54,55 ] such as PEO–PPO [ 32,56 ] or styrene– and diisobutylene–maleic acid copolymers. [ 57,58 ] Moreover, polymers have also been developed within the Dry Martini [ 59 ] version of the force field: examples include PEO, [ 60 ] PAMAM dendrimers, [ 61 ] and charged polysaccharide.…”
Section: Parametrization Strategiesmentioning
confidence: 99%
“…The structure and functioning of PEGylated and dendronized vesicles have been studied in many experimental works. In addition, the stability of such vesicles was studied with the help of coarse-grained simulations [ 17 , 18 , 19 ]. In these works, the vesicles obtained by the pre-insertion method were considered with modifying molecules being able to attach from both the outer and inner sides of the lipid vesicle.…”
Section: Introductionmentioning
confidence: 99%